Tiered Approaches to Rehabilitation Services in Education Settings: Towards Developing an Explanatory Programme Theory. (7th June 2023) - VanderKaay, Sandra; Dix, Leah; Rivard, Lisa; Missiuna, Cheryl; Ng, Stella; Pollock, Nancy; Whalen, Sandra Sahagian; Eisen, Isabel; Kyte, Christine; Phoenix, Michelle; Bennett, Sheila; Specht, Jacqueline; et al.
ABSTRACT: Rehabilitation services in education settings are evolving from pull-out interventions focused on remediation for children and youth with special education needs to inclusive whole-school tiered approaches focused on participation. A limited number of discipline-specific practice models for tiered services currently exist. However, there is a paucity of explanatory theory. This realist synthesis was conducted as a first step towards developing a middle-range explanatory theory of tiered rehabilitation services in education settings. The guiding research question was: What are the outcomes of successful tiered approaches to rehabilitation services for children and youth in education settings, in what circumstances do these services best occur, and how and why? An expert panel identified assumptions regarding tiered services. Relevant literature (n = 52) was located through a systematic literature review and was analysed in three stages. Several important contextual characteristics create optimal environments for implementing tiered approaches to rehabilitation services via three main mechanisms: (a) collaborative relationships, (b) authentic service delivery, and (c) reciprocal capacity building . Positive outcomes were noted at student, parent, professional, and systems levels. This first-known realist synthesis regarding tiered approaches to rehabilitation services in education settings advances understanding of the contexts and mechanisms that support successful outcomes.